Bioelectrical impedance analysis derived-phase angle as a pragmatic tool to detect protein energy wasting among multi-ethnic hemodialysis patients - Lim, Cordelia Kheng May; Lim, Jun Hao; Ibrahim, Imliya; Chan, Yoke Mun; Zakaria, Nor Fadhlina; Yahya, Rosnawati; Mat Daud, Zulfitri 'Azuan (Multidisciplinary Digital Publishing Institute, 2021)
Protein-energy wasting (PEW) is a devastating metabolic derangement that leads to increased morbidity and mortality in hemodialysis (HD) patients. This study aimed to determine the diagnostic test accuracy of bioelectrical impedance analysis derived-phase angle (PhA) in detecting PEW among HD patients. This was a multi-centre, cross-sectional study conducted amongst 152 multi-ethnic HD patients in Klang Valley, Malaysia. PEW was assessed using the International Society of Renal Nutrition and Metabolism criteria as the reference method. PhA was measured using a multi-frequency bioelectrical impedance spectroscopy at 50 kHz. Multiple and logistic regressions were used to determine factors associated with PhA and PEW diagnosis, respectively. A receiver operating characteristics curve analysis was used to establish the gender-specific PhA cut-offs to detect PEW. PEW existed in 21.1% of the HD patients. PhA was found as an independent predictor of PEW (adjOR = 0.308, p = 0.001), with acceptable to excellent discriminative performance (adjAUCmale = 0.809; adjAUCfemale = 0.719). Male patients had higher PhA cut-off compared to female patients (4.26° vs. 3.30°). We concluded that PhA is a valid and pragmatic biomarker to detect PEW in multi-ethnic Malaysian HD patients and a gender-specific cut-off is necessary, attributed to the gender differences in body composition.